Gambaran Hasil Pemeriksaan Kadar TSH dan T4 pada Wanita Subur di RS TK II Moh. Ridwan Meuraksa - Ashari, Sigit; Widhyasih, Retno Martini; Burhannudin, Burhannudin (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Thyroid disorders are defined as abnormalities in thyroid hormone levels, which can be observed from the results of examinations of thyroid stimulating hormone (TSH) and thyroxine (T4). These disorders often occur in women of childbearing age. The objective of this study is to ascertain the characteristics of the results of TSH and T4 examinations in fertile women at TK. II Moh. Ridwan Meuraksa Hospital will be the site of the study from February 2023 to February 2024, with a sample size of 75. This study employs a descriptive approach utilizing secondary data with a cross-sectional design. The results demonstrated that 14 individuals (18.7%) exhibited elevated TSH levels, 30 (40.0%) demonstrated normal levels, and 31 (41.3%) demonstrated low levels. About T4 levels, 31 individuals (41.3%) exhibited elevated levels, 30 (40.0%) demonstrated normal levels, and 14 (18.7%) demonstrated low levels. The classification of the results of the TSH and T4 examination is as follows: 31 individuals (41.3%) were identified as having hyperthyroidism, 30 individuals (40.0%) were identified as having Euthyroidism, and 14 individuals (18.7%) were identified as having Hypothyroidism. Most women of childbearing age in this study exhibited hyperthyroid results. A hyperthyroid condition indicates an overactive thyroid gland, resulting in elevated levels of thyroid hormones in the bloodstream and associated health complications. In contrast, hypothyroidism represents a range of clinical manifestations stemming from reduced or halted thyroid hormone production. It is therefore important to identify the risk factors associated with the incidence of hyperthyroidism to develop strategies for its prevention and to mitigate its effects, particularly in women of childbearing age, given the potential impact on reproductive function.